2004
DOI: 10.1161/01.hyp.0000114697.12750.d2
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Hypertension: Are Quality-Assurance Measures on Target?

Abstract: Abstract-Guideline committees recommend targets of treatment based on trial data on efficacy and effectiveness.Quality-assurance initiatives apply these parameters in the general practice setting. Therefore, targets must be feasible and achievable by the practicing physicians who are judged by these targets as goals for care. We evaluated 437 patients in the Rush University Hypertension Clinic using the Health Employer Data Information Set (HEDIS) measures for 2000 to assess goal achievement in a practice-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…57,58 Expanding drug coverage may be needed to ease financial barriers faced by patients with multiple conditions. 46,47 Drug utilization review programs could alert physicians to instances of suboptimal antihypertensive use 45 and performance standards 59 or "report cards" (eg, National Committee for Quality Assurance standards 60 ) could help monitor the impact of interventions on antihypertensive use in patients with comorbidities. A combination of all of these may be needed if the quality of hypertension care and the clinical outcomes of vulnerable elderly with comorbidities are to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Expanding drug coverage may be needed to ease financial barriers faced by patients with multiple conditions. 46,47 Drug utilization review programs could alert physicians to instances of suboptimal antihypertensive use 45 and performance standards 59 or "report cards" (eg, National Committee for Quality Assurance standards 60 ) could help monitor the impact of interventions on antihypertensive use in patients with comorbidities. A combination of all of these may be needed if the quality of hypertension care and the clinical outcomes of vulnerable elderly with comorbidities are to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…42,47,48 The proportion of diabetic, hypertensive patients treated and controlled in recent studies has been 20% to 25% using contemporary blood pressure criteria. 32,40,42,48,49 Chronic kidney disease represents another comorbidity associated with both difficult blood pressure control and high cardiovascular risk. Coresh et al 50 found that only 27% of hypertensive individuals with elevated serum creatinine in NHANES III had blood pressure Ͻ140/90 mm Hg.…”
Section: Prevalence Of Uncontrolled Hypertension In Epidemiological Smentioning
confidence: 99%
“…12,23,24 Even in our Hypertension Specialist Clinic in which 'goal-oriented management' has enabled us to successfully reduce DBP to o90 mmHg in uncomplicated hypertensives and to o85 mmHg in those with renal disease and/or diabetes mellitus in nearly 90% of our patients, we are only able to get SBP to goal in less than 60% of those patients. This finding that controlling DBP to goal is considerably easier than controlling SBP to goal has also been demonstrated in clinical trials which follow forcedtitration protocols.…”
Section: Chd (%)mentioning
confidence: 99%